Exploring perceived barriers and facilitators to using mobile phone technology for delivering HPV test results in malawi: a qualitative study with HPV-Screened women, healthcare providers, and health officials - John C. Chapola; Lameck Chinula; Wezzie Dunda; Agatha Bula; Bettie Kasonkanji; Jennifer H. Tang (BMC Public Health)
Abstract Background Cervical cancer, the fourth most common cancer among women globally, disproportionately affects low- and middle-income countries, such as Malawi, which has the world’s highest cervical cancer mortality rate. Efforts to implement human papillomavirus (HPV) testing for primary screening face challenges, including delays in delivering HPV results, hindering the retention of HPV-positive women in the care cascade. We conducted a study to identify the perceived barriers and facilitators to using mobile phones for delivering HPV results, aiming to improve the retention of HPV-positive women in care. We also explored the perspectives of women, health care providers, and health officials in Malawi’s cervical cancer screening program to provide a comprehensive view of challenges and opportunities. Methods This exploratory sub-study evaluated the perceived barriers and facilitators to delivering HPV screening results to women via mobile phones at four government-run health facilities in Lilongwe, Malawi. A trained research assistant conducted in-depth interviews (IDIs) with women who underwent HPV-based primary screening and received their HPV results, through a cluster randomized trial that compared two models of HPV-based screening. We also interviewed healthcare providers from these four health facilities and officials from the Lilongwe District Health Office (DHO). Data collected through the IDIs were recorded, transcribed, and translated. The transcripts were coded in NVivo 14 and analyzed using thematic analysis. Results Between January-March 2022, 35 participants completed the IDIs: 20 women who underwent HPV screening, 13 healthcare providers, and 2 DHO officials. The study findings revealed several critical factors influencing the implementation of HPV result delivery via mobile phone. Key challenges included low literacy and privacy concerns, which complicate the adoption of this method. Additionally, there was a perceived risk of unintended receipt of HPV results by partners or family members, in that many women do not own mobile phones and rely on shared handsets. However, incentives such as airtime, functional phones, and appropriate equipment could support healthcare providers in delivering effective communication and healthcare services. Conclusion While mobile phone communication has the potential to enhance HPV result delivery, its success relies on overcoming perceived barriers such as low literacy, privacy concerns, inadequate resources, and the need for a supportive implementation environment.